Autoeficácia, satisfação e disposição docentes na atuação de educadores em projetos sociais de Bauru e Ibitinga - Roncada, Luan Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present project aims to investigate the self-efficacy of educators in social projects and to highlight the points that influence the ability to continue the teaching career and the satisfaction of the teachers themselves, since self-efficacy influence directly self-efficacy and motivation of the students. Another objective is to analyze and observe the use of the content of the corporal practices in these environments, using popular games and children's games, in the pedagogical action with the students. This research, as a starting point for the theoretical foundation in Bandura's (1997, 2001) Cognitive Social Theory (CTS), in the specificity of the concept and appropriation of the construct of self-efficacy, of what is more specific and greater in the database for the context in the question: the self-efficacy of educators in acting in social projects. For accomplish this study, it was used 04 (four) instruments of data collection: a) participant characterization questionnaire (PCQ), with information and demographic data and all the descriptive statistics of the research subjects; b) Teacher self-efficacy scale (likert type) - Scale A; c) Scale of sources of self-efficacy - Scale B; and d) Questionnaire on Motivational Aspects (QMA), with reference to popular games. Participated in this study 23 (twenty-three) educators from five social projects of the city of Bauru and Ibitinga, in the state of São Paulo inner region. Only participated the educators who agreed with the adopted procedures in the study, and signed the Free and Informed Consent Form. The results applied to the Kruskal Wallis test did not present significant differences between the groups, perhaps due to the low number of participants used in the study, therefore, it is necessary that we carry out other studies with a number of participants with a larger sample than in the present study... (Complete abstract electronic access below)

O presente projeto tem como objetivo investigar a autoeficácia dos educadores em projetos sociais e destacar os principais pontos que influenciam na disposição em dar continuidade à carreira docente e satisfação profissional dos mesmos enquanto atuam, visto que a autoeficácia destes influencia diretamente na autoeficácia e motivação dos alunos. Outro objetivo é analisar e observar a utilização do conteúdo das práticas corporais nestes ambientes, fazendo uso dos jogos populares e brincadeiras infantis, na atuação pedagógica com os alunos. Esta investigação, terá como ponto de partida o embasamento teórico nos referenciais da Teoria Social Cognitiva (TSC) de Bandura (1997, 2001), na especificidade do conceito e apropriação do constructo da autoeficácia, de maneira mais específica e maior robustez no banco de dados para o contexto em questão: a autoeficácia dos educadores na atuação em projetos sociais. Para a realização deste estudo, foi feito o uso de 04 (quatro) instrumentos de coleta de dados: a) questionário de caracterização do participante (QCP), com informações e dados demográficos e toda a estatística descritiva dos sujeitos da pesquisa; b) Escala de autoeficácia do professor (tipo likert) - Escala A; c) Escala das fontes de autoeficácia - Escala B; e d) Questionário Associado sobre Aspectos Motivacionais (QAAM), com respeito à atuação em jogos populares e brincadeiras. Participaram do presente estudo 23 educadores que atuam em cinco projetos sociais localizados na cidade de Bauru e Ibitinga, interior do estado de São Paulo. Somente participaram do estudo os educadores que concordaram com os procedimentos adotados, e assinaram um Termo de Consentimento Livre e Esclarecido. Os resultados aplicados ao teste Kruskal Wallis não apresentaram diferenças significativas entre os grupos, talvez pelo baixo número de participantes ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Auto-eficácia; Educadores - Bauru (SP); Pratica de ensino - Aspectos sociais; Self-efficacy